The Role of Financing Risk in Moderating the Relationship between Bank Size and Health in Islamic Commercial Banks for the Period 2021-2023 - Rena Soraya; Akhmadi Akhmadi; Eka Purwanda (Institute of Advanced Knowledge and Science, 2025)
This study was conducted to explore and examine the nature of the ability of Islamic Commercial Banks to stabilize the level of bank health as proxied by the Capital Adequacy Ratio (CAR) by considering the value of bank size, which in this case is studied in more depth by using financing risk as a moderating variable and operations efficiency as a control variable in Islamic Commercial Banks for the period 2021-2023. This study uses secondary data from quarterly financial reports published by each Islamic Commercial Bank with a sample size of 10 Islamic Commercial Banks. A sampling technique using purposive sampling was used. The data analysis used is panel data regression using the Random Effect Model (REM). The data analysis technique used is the Moderated Regression Analysis (MRA) panel data test. The results of this study indicate that Size has a significant negative effect partially on Bank Health (CAR). Financing Risk moderates the impact of Size on CAR. The interaction of financing risk (NPF) with Size moderates the effect of Size on bank health (CAR). The results show this study's role of financing risk as a quasi-moderation.